Reconceptualizing The Dispute Resolution Model for Village Head Elections Towards Independent and Fair Elections - Zainudin, Arif; Safa’at, Muchamad Ali; Anshari, Tunggul; Susmayanti, Riana (Audito Comparative Law Journal (ACLJ), 2025)
This study aims to reconceptualize the dispute resolution model for Pilkades, which has traditionally been handled by regents/mayors (Bupati/Walikota), a mechanism criticized for being prone to political interference and lacking principles of justice and independence. The election of village heads (Pilkades) represents a form of local democracy, reflecting community participation in village governance. However, its implementation is often marred by disputes over election results, leading to social tensions and conflicts. Using normative and empirical legal approaches, this research analyzes the weaknesses in the existing dispute resolution procedures and proposes an alternative model that is fairer and more transparent. The findings reveal that entrusting dispute resolution authority to regents/mayors poses significant challenges, such as political bias, unclear legal mechanisms, and insufficient community involvement. Therefore, an independent and neutral institution is required to handle Pilkades disputes by emphasizing the principles of justice and transparency. This study recommends the establishment of a special body through regional regulations to manage dispute resolution independently, involving community elements and utilizing digital technology to enhance process transparency. By reconstructing the Pilkades dispute resolution model based on the principles of justice, transparency, and independence, this approach is expected to strengthen village democracy and prevent prolonged conflicts.